FORMULATION AND EVALUATION OF CONTROLLED RELEASE MUCOADHESIVE MATRIX TABLETS: ASSESSMENT OF MYRRH OLEO GUM RESIN AS A NATURAL PHARMACEUTICAL EXCIPIENT (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Mucoadhesive polymer owing to its binding capacity with gastric mucin prolongs the gastric residence time and thereby increased drug bioavailability. In the present study, oral controlled release mucoadhesive matrix tablets have been developed for domperidone as model drug using natural mucoadhesive material myrrh oleo gum resin (MOGR).The tablets were formulated with the natural polymer in different concentration (5, 10, 15 and 20 % w/w) employing direct compression technology. The prepared batches were evaluated for tablet parametric test (drug assay, diameter, thickness, hardness and tensile strength), swelling index, mucoadhesive strength (using texture analyser) and in vitro drug release studies. Accelerated stability studies were also conducted on all the prepared batches. The tensile strength increases from 0.973±0.09 to 1.687±0.11 MN/m2 and mucoadhesive strength from19.868 to 49.778 N with the increase in natural polymer concentration from 5 to 20 % (M1 to M4). Swelling index of natural polymer was testified towards proliferation by together increasing gum concentration and the time period. The release kinetic and mechanism of release were calculated by fitting in vitro release data in various models demonstrating that release follows zero order and Hixson Crowell cube root law. The release exponent (n) ranges in between 0.5889 to 0.7389 indicating multiple release mechanisms possibly the combination of diffusion and erosion. Accelerated stability studies demonstrate no significant change in the tensile strength, mucoadhesive strength and drug assay. These research outcomes clearly specify the potential of MOGR to be used as binder, release retardant and mucoadhesive natural material in tablet formulations.